Valeric Biofuels from Biomass‐Derived γ‐Valerolactone: A Critical Overview of Production Processes - Martínez Figueredo, Karla Geraldine (2023)
This review analyzes critically the production of valeric biofuels from γ-valerolactone, a relevant biomass-derived platform molecule. Initially, the main properties of valeric esters as fuels for spark- and compression-ignition engines are summarized. Then, catalytic routes to valeric esters from γ-valerolactone are meticulously analyzed, describing the acid- and metal-catalyzed reactions taking part in the tandem catalysis. Only works focused on the production of the valeric biofuels were considered, excluding the cases where these esters were observed in minor amounts or as byproducts. The role of the appropriate selection of the support, catalytic species, catalyst preparation and experimental conditions on the valeric ester productivity are thoroughly commented. Finally, some concluding remarks and perspectives are given, mentioning the areas where additional efforts must be done in order to turn the dream of a massive and renewable valeric biofuel production into a reality.